2014
DOI: 10.1186/2193-1801-3-571
|View full text |Cite
|
Sign up to set email alerts
|

Systemic levels of the endothelium-derived soluble adhesion molecules endocan and E-selectin in patients with suspected deep vein thrombosis

Abstract: The initial evaluation of patients with suspected deep vein thrombosis includes the use of biomarkers reflecting activation of the coagulation system. However, the thromboembolic process and neighboring inflammatory responses also affect endothelial cells, and endothelial cell markers may therefore be altered by the disease. In the present population-based single-center study, we investigated the plasma levels of the endothelium-specific biomarkers soluble E-selectin and endocan in a consecutive and unselected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…We also showed that elevated sE-selectin levels were associated with PTS grade. Two previous studies evaluated sEselectin levels during the acute phase of DVT and showed no association between DVT and increased sE-selectin levels [20,38]. Our findings are interesting considering that we demonstrated endothelial dysfunction even a long time after the acute DVT episode, and this seems to be associated with PTS severity.…”
Section: Discussionsupporting
confidence: 51%
“…We also showed that elevated sE-selectin levels were associated with PTS grade. Two previous studies evaluated sEselectin levels during the acute phase of DVT and showed no association between DVT and increased sE-selectin levels [20,38]. Our findings are interesting considering that we demonstrated endothelial dysfunction even a long time after the acute DVT episode, and this seems to be associated with PTS severity.…”
Section: Discussionsupporting
confidence: 51%
“…A study [42] investigated plasma levels of the endocan and E-selectin; the combined analysis of these biomarkers (either the two markers alone or together with D-dimer and CRP) could be used to identify patient subsets with different frequencies of DVT in a group of consecutive/unselected 120 patients admitted to hospital with suspected DVT.…”
Section: Other Inflammatory Diseases and Endocanmentioning
confidence: 99%
“…It has been suggested to be a new biomarker for endothelial dysfunction and PE (751, 752). It would appear, however, to be a rather less specific inflammatory biomarker (753, 754) and is associated with a variety of diseases, including chronic kidney disease (755, 756) and cardiovascular disease (755). Most pertinently from our perspective, it is also raised strongly during sepsis (757760).…”
Section: Proteomic and Similar Biomarkers – Circulating And Placentalmentioning
confidence: 99%